2002
DOI: 10.1128/jvi.76.1.195-207.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Motif in the C Terminus of Herpes Simplex Virus Regulatory Protein ICP4 That Contributes to Activation of Transcription

Abstract: Expression of most viral genes during productive infection by herpes simplex virus is regulated by the viral protein ICP4 (also called IE175 or Vmw175). The N-terminal portion of ICP4 contains well-defined transactivation, DNA binding, and dimerization domains that contribute to promoter regulation. The C-terminal half of ICP4 contributes to the activity of ICP4, but the functional motifs have not been well mapped. To localize functional motifs in the C-terminal half of ICP4, we have compared the relative spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…ICP4, the sole immediate–early protein in EHV‐1, is essential for viral replication (Garko‐Buczynski, Smith, Kim, & O'Callaghan, 1998). There were four non‐synonymous changes in this region when compared to the consensus EHV‐1 sequence, but it is not known whether this has any functional outcome, although the C ‐terminus of HSV‐1 ICP4 is thought to enhance the functions of the transactivation domain located at the N ‐terminus (Bruce & Wilcox, 2002; Wagner, Bayer, & Deluca, 2013). A similar, but not identical, recombination event between EHV‐1 and EHV‐4 has been reported in the same ORF in an EHV‐1 strain isolated in Japan (Pagamjav, Sakata, Matsumura, Yamaguchi, & Fukushi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…ICP4, the sole immediate–early protein in EHV‐1, is essential for viral replication (Garko‐Buczynski, Smith, Kim, & O'Callaghan, 1998). There were four non‐synonymous changes in this region when compared to the consensus EHV‐1 sequence, but it is not known whether this has any functional outcome, although the C ‐terminus of HSV‐1 ICP4 is thought to enhance the functions of the transactivation domain located at the N ‐terminus (Bruce & Wilcox, 2002; Wagner, Bayer, & Deluca, 2013). A similar, but not identical, recombination event between EHV‐1 and EHV‐4 has been reported in the same ORF in an EHV‐1 strain isolated in Japan (Pagamjav, Sakata, Matsumura, Yamaguchi, & Fukushi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence homologies, alphaherpesvirus ICP4 orthologs are divided into regions I to V from the amino to the carboxy terminus (13,17,43,84). BHV-5 and BHV-1 ICP4 are most similar (90 to 100% amino acid identity) within regions II and IV.…”
Section: Resultsmentioning
confidence: 99%
“…The C-terminal regions of ICP4 analogs are highly conserved among different alphaherpesviruses (9,57). The available data indicate that even small mutations in the C-terminal domain of ICP4 significantly alter the biological activities of the protein (6,10). Studies are under way to determine the region within the C-terminal domain of ICP4 involved in DNA-dependent oligomerization to explore its contribution activation independent of other functions in the C-terminal region of ICP4.…”
Section: Discussionmentioning
confidence: 99%
“…ICP4 negatively regulates the ICP4 promoter (12, 41), latency-associated promoter (3), and L/ST promoter (5, 59) and activates most of the early and late genes of the virus (12,16,22,41,45,57,60). Genetic and biochemical analyses revealed that ICP4 contains discrete domains responsible for DNA binding, nuclear localization, and transcriptional regulation (6,14,43,44,49,51). ICP4 is a dimer in solution (39) and probably functions as a dimer in DNA binding and transcriptional regulation (40,50).…”
mentioning
confidence: 99%